Designing of Parking Spaces Taking into account the Parameters of Design Vehicles in Russia - Miroslava Mikusova; Jamshid Abdunazarov; Joanna Zukowska; Alisher Usmankulov (Communications - Scientific letters of the University of Zilina, 2020)
Nowadays, in all the cities, there is an acute problem of a lack of parking spaces. The number of vehicles are becoming more and more larger, not only in megacities, but in small cities of the country, as well and there are no more parking places - the pace of solving the problem is several times slower than the rate of the transport growth among the citizens. The article is dedicated to the determination of the optimum sizes parking place for designing vehicles on a parking space, which is an element of the roads. The optimum amount parking places are determined on examples of the passenger cars and trucks. The results of research on dimensioning of parking spaces and recommendations to use the results for design of objects of transportation infrastructure are presented. According to the research, authors included the term "design vehicle" and gave its definition. The authors developed a template for 7 types of design vehicles and their sizes and also recommended sizes for longitudinal parking for each of their design vehicles. The optimum parking plot angles are determined, as well.